2015
DOI: 10.1037/apl0000023
|View full text |Cite
|
Sign up to set email alerts
|

Till stress do us part: On the interplay between perceived stress and communication network dynamics.

Abstract: This study of perceived stress and communication networks fills 2 theoretical gaps in the literature: First, drawing predominantly on conservation of resource theory and faultline theory, we demonstrate the role of stress as an "engine of action" in network evolution. Second, we extend the stress literature to the interpersonal domain by arguing that others' levels of stress influence the individual's communication network, and this, in turn, changes his or her stress level. At 3 time points, we evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 82 publications
6
74
0
Order By: Relevance
“…This finding is in line with two cross‐sectional studies confirming that formal and informal social support serves a core resource among former USSR immigrants in Israel (Lerner, Kertes, & Zilber, ; Mirsky et al, ). As argued in the preceding texts that social connections serve as resource passageways (Kalish et al, ), and that reports of supervisor support among immigrants who are in greater need of resources may indicate that such resource passageways are indeed utilized. These differences between immigrants and natives accentuate the importance of considering immigration status among study participants, especially in samples that constitute a large proportion of immigrants.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in line with two cross‐sectional studies confirming that formal and informal social support serves a core resource among former USSR immigrants in Israel (Lerner, Kertes, & Zilber, ; Mirsky et al, ). As argued in the preceding texts that social connections serve as resource passageways (Kalish et al, ), and that reports of supervisor support among immigrants who are in greater need of resources may indicate that such resource passageways are indeed utilized. These differences between immigrants and natives accentuate the importance of considering immigration status among study participants, especially in samples that constitute a large proportion of immigrants.…”
Section: Discussionmentioning
confidence: 93%
“…Theories of resources (e.g., Conservation of Resources Theory, Hobfoll, 2001;Hierarchy of Needs, Maslow, 1943) maintain that individuals are driven to obtain and retain resources. Thus, obtaining resources can enhance health (Hobfoll, 2011), while inability to obtain or retain resources can cause stress (Kalish, Luria, Toker, & Westman, 2015) and impair the capacity to engage in higher level behaviours (Maslow, 1943). Consequently, we predicted that health behaviours pertaining to basic physiological needs, such as adequate sleep or food consumption that fulfils nutritional requirements, may be necessary in order to provide individuals with sufficient resources for engaging in higher level behaviours (e.g., physical exercise or medical check-ups).…”
Section: Hypothesesmentioning
confidence: 99%
“…However, although interpersonal interactions are proposed as the mechanism through which the convergence of emotions occurs, actual interpersonal interactions among employees have largely remained unexplored in research on burnout contagion. With the exception of a study conducted by Kalish, Luria, Toker, and Westman (), previous studies have measured exposure to levels of burnout among colleagues through self‐report scales that either measured perceptions of burnout or aggregated individual burnout scores at a team level. This study aimed to fill this gap in the literature and open the black box that elucidates the process of burnout contagion.…”
Section: Introductionmentioning
confidence: 99%
“…The focus remains largely on the individual and his/her perceptions of others. However, a study by Kalish et al () was an exception and demonstrated the value of taking a truly interpersonal perspective. The results showed that stress levels affect communication patterns: Individuals with higher stress levels were less likely to engage in interaction with new colleagues and primarily maintained existing communication ties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation